Understanding, Explaining and Interpreting the Process of Shaping a Woman’s Subjectivity on the Example of Bell Hooks Autobiography. A Study of Women’s Autobiographies in the Context of Thomas and Znaniecki’s Research - Ostaszewska, Aneta (Italian Sociological Review, 2020)
The aim of the paper is to reflect on bell hooks’ autobiographies in the context of women’s process of self-empowerment. Following the principle of the humanistic coefficient (Znaniecki) and recognizing autobiography as a significant source in social research (Thomas, Znaniecki), my focus is to understand, explain and interpret the process of shaping a woman’s subjectivity by analysing bell hooks’ autobiographical essays. I am interested in her autobiography as a life story of a black woman, whose experiences have been shaped by racial segregation and desegregation in the 1960s and 1970s in the USA and for whom writing autobiography has been a manifestation of speaking with her own voice.